Summary of the Proceedings of Asian Oceanian Radiology Forum 2025: Key Challenges in Radiology Clinical Practice across the Asia-Oceania Region - Indian Radiological and Imaging Association (Indian Journal of Radiology and Imaging, 2025)
The Asian Oceanian Radiology Forum at the AOCR 2025 discussed the key challenges in clinical radiology practice. The participating societies were invited to submit their report addressing the current situation in their country or region. The session also focussed on identifying common bottlenecks and possible solutions including financial sustainability, expansion of training and inclusion of articial intelligence (AI).
Keywords: Artificial Intelligence; Workforce; Infrastructure; Teleradiology; Sustainability